The effect of holstein bulls’kappa-casein gene genotype on the productive longevity of their female offspring in the republic of Bashkortostan - Yumaguzin Idris; Aminova Albina; Kosilov Vladimir; Sedykh Tatiana (BIO Web of Conferences, 2021)
Increased productivity in the industry can be achieved by breeding for productive longevity through searching and using genetic markers. The study analysed the data of 1476 animals with at least one completed lactation. Depending on the linear affiliation and kappa-casein gene genotype of servicing bulls, their female offspring were divided into 4 groups. The CSN3 A allele frequency in the studied bulls was 81.91%, the CSN3 B allele was 18.09%. The highest frequency of the desired CSN3 B allele in the servicing bulls-producers of the Reflection Sovering line was 20.83%, which is 3.69% more than in the bulls of the Vis Back Ideal line. The animal life length analysis showed that the female progeny of bulls from the Reflection Sovering line (2.46 lactation), especially those with the CSN3 AB genotype (2.59 lactation), had the longest life. The offspring of CSN3AB genotype bulls of the Reflection Sovering line had the highest lifetime milk yield (18490 kg). The CSN3AB genotype cows of the Reflection Sovering line had the highest average milk yield on the 1st day of a cow’s life of 9.05 kg.